1992
DOI: 10.1007/bf02447832
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by nisin of K+ uptake in a sensitivePediococcus sp. strain

Abstract: SUMMARYA nisin-sensitive strain of Pediococcus sp possessed an uptake system for K + which was apparently dependent on metabolic energy and ATPase activity. K + uptake rate was dependent on the glucose and K + eoncentratious and showed approximately Michaelis-Menten kinetics with respect to both of these variables with K t values of 1.2 mM and 599/xM respectively.The presence of nisin inhibited K + uptake with the percentage inhibition proportional to the nisin activity,. Total inhibition occurred at between 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This latter ion is involved in cell turgor pressure maintenance, enzyme activation, and intracellular pH homeostasis regulation (Bakker 1993). Consequently, cell damage and changes in membrane permeability could be indirectly determined by potassium movements (White et al . 1992; Ray 1993; Abee et al .…”
mentioning
confidence: 99%
“…This latter ion is involved in cell turgor pressure maintenance, enzyme activation, and intracellular pH homeostasis regulation (Bakker 1993). Consequently, cell damage and changes in membrane permeability could be indirectly determined by potassium movements (White et al . 1992; Ray 1993; Abee et al .…”
mentioning
confidence: 99%
“…neutral pH maintain a proton motive force (4p) of about -120 mV (6), and energized, growing cells maintain a somewhat higher Ap (about -160 mV [4]), there are only a few reports demonstrating 4p-coupled metabolic activities in this organism (16,22). That the 4p in L. monocytogenes is dissipated by nisin (4,5), pediocins (5)(6)(7), and other bacteriocins (16) suggests that bacteriocin-mediated inhibition of Listeria spp.…”
mentioning
confidence: 99%
“…Various investigators have suggested that bacteriocin-mediated deenergization of the cytoplasmic membrane was responsible for reduced rates of amino acids and potassium uptake by sensitive cells (22). Recently, Abee et al (1) showed that lactacin F, a two-component bacteriocin produced by Lactobacillus johnsonii, caused phosphate efflux, resulting in hydro-lysis of intracellular ATP and decreased growth rates in sensitive cells.…”
mentioning
confidence: 99%